Evaluating the Potential of Developing Cross-Platform Mobile Applications - Yakubovich, Mikhail (My University, 2013)
The mobile market is rapidly growing along with the constant increase in handheld devices per household. This trend affects IT consultancy companies whose clients often request applications for mobile operating systems such as iOS, Android and Windows Phone. Such companies strive to decrease the development time and present the customer with a satisfying solution that is delivered on time. In order to decrease the time-to-market and thus the cost of the final product, companies seek to develop applications independent of the target mobile operating system by using a cross-platform approach. This approach can eliminate the increased effort that normally comes with developing a separate application for each mobile operating system, providing a more efficient solution. This master thesis investigates two common cross-platform tools (CPTs), namely, Xamarin and Unity. In addition we examine the approach of sharing a core code base of a mobile application between multiple platforms. The purpose is to determine which alternative CPT is more suitable for the development of portable mobile applications. The Analytic Hierarchy Process methodology is used to give a high-level quality analysis of the CPTs and to select the most suitable candidate to use to develop the target application.
Keywords: Data- och informationsvetenskap; Computer and Information Science